2022
DOI: 10.1055/a-1843-9855
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epicatechin Reverses Glucose Intolerance in Rats Housed at Thermoneutrality

Abstract: Diabetes is a life-threatening and debilitating disease with pathological hallmarks, including glucose intolerance and insulin resistance. Plant compounds are a source of novel and effective therapeutics, and the flavonoid (−)-epicatechin, common to popular foods worldwide, has been shown to improve carbohydrate metabolism in both clinical studies and preclinical models. We hypothesized that (−)-epicatechin would alleviate thermoneutral housing-induced glucose intolerance. Male rats were housed at ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In the current study, however, there was no evidence of a difference in PGC-1α expression or content by sex or diet. This interstudy difference may be due to housing temperature differences between studies (22 • C room temperature versus 30 • C rat thermoneutrality), which has been shown to alter metabolic phenotypes [33]. Recent work highlights the complexity of mitochondrial biogenesis, suggesting vital roles for signaling networks beyond PGC-1α [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, however, there was no evidence of a difference in PGC-1α expression or content by sex or diet. This interstudy difference may be due to housing temperature differences between studies (22 • C room temperature versus 30 • C rat thermoneutrality), which has been shown to alter metabolic phenotypes [33]. Recent work highlights the complexity of mitochondrial biogenesis, suggesting vital roles for signaling networks beyond PGC-1α [34].…”
Section: Discussionmentioning
confidence: 99%